2019
DOI: 10.1165/rcmb.2017-0405oc
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular C3 Protects Human Airway Epithelial Cells from Stress-associated Cell Death

Abstract: The complement system provides host defense against pathogens and environmental stress. C3, the central component of complement, is present in the blood and increases in the bronchoalveolar lavage fluid following injury. We recently discovered that C3 is taken up by certain cell types and cleaved intracellularly to C3a and C3b. C3a is required for CD4+T cell survival. These observations made us question if complement operates at environmental interfaces, particularly in the respiratory tract. We found that air… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
99
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 67 publications
(100 citation statements)
references
References 62 publications
1
99
0
Order By: Relevance
“…Specifically, the high resolution afforded by GRO-seq allowed us to discover additional target genes in which dex + TNF treatment resulted in higher levels of RNAPII activity than was evident with dex or TNF alone. Novel targets of glucocorticoid-TNF cooperation include PGM3, whose deficiency is associated with elevated IgE levels and asthma (Yang et al 2014), FTH1, which protects against TNF-mediated apoptosis (Pham et al 2004), and C3, a traditionally pro-inflammatory gene that was recently reported to suppress stress-associated apoptosis in BEAS-2B airway epithelial cells (Kulkarni et al 2019). The anti-inflammatory functions of each of these genes further implicate cooperative gene regulation by the GR and NF-kB as an important mechanistic underpinning of repression of inflammation and cell injury by glucocorticoids.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, the high resolution afforded by GRO-seq allowed us to discover additional target genes in which dex + TNF treatment resulted in higher levels of RNAPII activity than was evident with dex or TNF alone. Novel targets of glucocorticoid-TNF cooperation include PGM3, whose deficiency is associated with elevated IgE levels and asthma (Yang et al 2014), FTH1, which protects against TNF-mediated apoptosis (Pham et al 2004), and C3, a traditionally pro-inflammatory gene that was recently reported to suppress stress-associated apoptosis in BEAS-2B airway epithelial cells (Kulkarni et al 2019). The anti-inflammatory functions of each of these genes further implicate cooperative gene regulation by the GR and NF-kB as an important mechanistic underpinning of repression of inflammation and cell injury by glucocorticoids.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, this rapid internalization of C3 is likely to alter the proinflammatory responses when an exogenous source of C3 is made available (e.g., in the context of barrier disruption and associated plasma leak in acute lung injury) and accelerated turnover from C3 to C3(H 2 O) in the context of ongoing inflammation (101). The recent discovery that intracellular C3 protects human airway epithelial cells (AECs) from stress-associated death may also have implications for COVID-19 (102). In this study, AECs were unique compared with other cell types in containing large intracellular stores of de novo-synthesized C3.…”
Section: Intracellular Complement Viral Defense: the Complosomementioning
confidence: 99%
“…The complement system comprises an intricately regulated set of more than 40 proteins that are ancient components of the vertebrate immune system ( 1 ). Complement can act both in the “fluid-phase” of blood as well as at a cellular-molecular level in tissues throughout the body ( 1 , 2 ). There are three well-characterized pathways of complement proteolysis and activation: the alternative, classical, and lectin pathways.…”
mentioning
confidence: 99%